Ceria-Based Mixed Oxide Supported Nano-Gold as an Efficient and Durable Heterogeneous Catalyst for Oxidative Dehydrogenation of Amines to Imines Using Molecular Oxygen - Bashir Ahmad Dar; Meena Sharma; Baldev Singh (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
The present work is intended to determine the catalytic activity of Mixed Oxide supported gold for aerobic oxidative dehydrogenation of amines to imines using Ceria as a main constituent of the each support. The model catalysts Au/CeO2:TiO2 Au/CeO2:SiO2, Au/CeO2:ZrO2 and Au/CeO2:Al2Os were prepared by deposition co-precipitation method and deposition of gold was determined by EDEX analysis. The supported nano-gold catalyzes the dehydrogenation of secondary amines to imines without loss of activity. On recycling good amount of product yield is obtained. Oxidation of secondary amines to imines is carried at 100˚C and almost 90 % conversion was obtained with >99% selectivity. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)